2021
DOI: 10.21203/rs.3.rs-418184/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Coalescence and Isospin Symmetry on the Freezeout of Light Nuclei and Their Anti-particles

Abstract: The transverse momentum spectra of light nuclei (deuteron, triton and helion) produced in various centrality intervals in Gold-Gold (Au-Au), Lead-Lead (Pb-Pb) and proton-Lead (p-Pb) collisions, as well as in inelastic (INEL) proton-proton (pp) collisions are analyzed by the blast wave model with Boltzmann Gibbs statistics. The model results are nearly in agreement with the experimental data measured by STAR and ALICE Collaborations in special transverse momentum ranges. We extracted the bulk properties in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…We found that the kinetic freeze out temperature (T 0 ) is larger in central collisions than in peripheral collision and this is in consistent with [59,60,61,63,64,65], but disagrees with [54,62]. Furthermore, it is observed that triton freezeout earlier than deuteron and antideuteron and this result is consistent with [80,81], and has less values of β T than deuteron and-anti-deuteron which exhibits the mass dependence of T 0 and β T . The lower values of β T for triton is due to the fact that triton can be left behind in the system evolution process due to their large masses.…”
Section: Collisionssupporting
confidence: 54%
“…We found that the kinetic freeze out temperature (T 0 ) is larger in central collisions than in peripheral collision and this is in consistent with [59,60,61,63,64,65], but disagrees with [54,62]. Furthermore, it is observed that triton freezeout earlier than deuteron and antideuteron and this result is consistent with [80,81], and has less values of β T than deuteron and-anti-deuteron which exhibits the mass dependence of T 0 and β T . The lower values of β T for triton is due to the fact that triton can be left behind in the system evolution process due to their large masses.…”
Section: Collisionssupporting
confidence: 54%
“…Again Pythia has closer value at √ s = 0.9 TeV then the HIJING and QGSJET which have higher and lower values respectively while in case of √ s = 2.36 TeV, all models have lower values than the data. To see the variation of the effective temperature T (T B and T q ), figure 7 shows the values of T extracted from the three-component function [equation (3)] and the q-dual function [equation (5)] as a function of |η| at √ s = 0.9 (a) and 2.36 TeV (b). It is clear from the graphs that the values of T B is larger compared to T q as the latter is affected by q.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The study of particle collisions itself is a complex phenomenon that makes it difficult to understand the geometry and measure global or bulk properties of the interactions. Besides experimental measurements, it is therefore important to use theoretical models or analytic functions to deduce different parameters such as the effective temperature (T ), kinetic freeze-out temperature (T 0 ), average transverse flow velocity ( β T or β T in simple term) and kinetic freeze-out volume (V) [1][2][3][4] based on experimental data. Here, T contains the contribution of thermal motion reflected by T 0 and transverse flow effect reflected by β T .…”
Section: Introductionmentioning
confidence: 99%